Green Marketing Dynamics : Analyzing Greenwashing, Brand Trust, and Consumer Purchase Intentions - Hazarika, Udipta Shankar; Khandai, Sujata; Kohli, Harpuneet Singh (Indian Journal of Marketing, 2025)
Green marketing has gained more and more popularity as companies advertise green products, but greenwashing as a phenomenon has put tremendous challenges on the creation of consumer confidence. Purpose : The research question examined in this paper explored greenwashing, green brand equity, green brand trust, green brand image, green brand confusion, and purchase intention in order to explain the overall impact of this relationship on consumer behavior. Methodology : The quantitative survey design was used in order to investigate the effect of greenwashing on consumer trust and brand loyalty. The authors also measured the roles of brand equity and brand image on the preference for green purchase behavior. Findings : The findings revealed that green brand trust and equity reduced the negative effects of greenwashing and brand confusion, and thus, enhanced purchase intentions. These results would offer practical information to brands that are trying to find sustainable ways to survive. Practical Implications : The paper suggested that companies should shift their attention to authentic and transparent green claims so that they can address customer confusion and build trust. Retailers could promote the value of the brand and stimulate the purchase of true eco-friendly products by integrating open communication and applying certified eco-labels. Originality : This study is unique as it examined the impact of greenwashing and determinants of green brands on consumer purchase intentions in offline retail contexts, which have had minimal studies in previous literature.